Application of Choi—Williams Reduced Interference Time Frequency Distribution to Machinery Diagnostics - Howard A. Gaberson (Shock and Vibration)
This article discusses time frequency analysis of machinery diagnostic vibration signals. The short time Fourier transform, the Wigner, and the Choi–Williams distributions are explained and illustrated with test cases. Examples of Choi—Williams analyses of machinery vibration signals are presented. The analyses detect discontinuities in the signals and their timing, amplitude and frequency modulation, and the presence of different components in a vibration signal.